Getting to Know the Gut Microbial Diversity of Metropolitan Buenos Aires Inhabitants - Belforte, Fiorella Sabrina; Fernandez, Natalie; Tonín Monzón, Francisco; Rosso, Ayelén Daiana; Quesada, Sofía; Cimolai, María Cecilia; Millán, Andrea; Cerrone, Gloria Edith; Frechtel, Gustavo Daniel; Burcelin, Rémy; Coluccio Leskow, Federico; Penas-Steinhardt, Alberto (Frontiers in Microbiology, 2019)
In recent years, the field of immunology has been revolutionized by the growing understanding of the fundamental role of microbiota in the immune system function​. The immune system has evolved to maintain a symbiotic relationship with these microbes. The aim of our study was to know in depth the uncharacterized metagenome of Buenos Aires (BA) city population and its metropolitan area, being the second most populated agglomeration in the southern hemisphere. For this purpose, we evaluated 30 individuals (age: 35,23 ± 8,26 years and BMI: 23,91 ± 3,4 kg/m2), from the general population of BA. The hypervariable regions V3-V4 of the bacterial 16S gene was sequenced by MiSeq-Illumina system, obtaining 47526 ± 4718 sequences/sample. The dominant phyla were Bacteroidetes, Firmicutes, Proteobacteria, Verrucomicrobia and Actinobacteria. Additionally, we compared the microbiota of BA with other westernized populations (Santiago de Chile, Rosario-Argentina, U.S.-Human-microbiome-project, Bologna-Italy) and the Hadza population of hunter-gatherers. The unweighted UniFrac, clusterized all westernized populations leaving the hunter-gatherer population from Hadza out. In particular, Santiago de Chile's populations turns out to be the closest to BA's, principally by the presence of Verrucomicrobiales of the genus Akkermansia. These microorganisms have been proposed as a hallmark of a healthy gut. Finally, westernized populations showed more abundant metabolism related KEEG pathways than hunter-gatherers, including carbohydrate metabolism (amino sugar and nucleotide sugar metabolism), amino acid metabolism (alanine, aspartate and glutamate metabolism), lipid metabolism, biosynthesis of secondary metabolites and sulfur metabolism. These findings contribute to promote research and comparison of the microbiome in different human populations, in order to develop more efficient therapeutic strategies for the restoration of a healthy dialogue between host and environment.